Regional impacts of infrastructural programmes: ex-post assessment methodologies revisited - Emília Malcata Rebelo (2010)
This communication inserts in the scope of the increasing planning concerns with the economic evaluation of public investments, within a regional perspective in order to fukfill efficiency criteria.The research reported here settles, on the one hand, in a revision of recent literature about this issue and, on the other, in a case study applied to the Portuguese Northern Region.The study develops through the following steps: (i) ex-post analysis of the aggregated impact of public investments in infrastructures and public works, (ii) evaluation of the degree of attainment of the ex-ante settled goals of efficiency, economic growth and inter-regional fairness, (iii) development of an integrated set of decision-support tools concerning the aggregated ex-post evaluation of these kinds of investments.It is expected that this assessment of the impact of past public investments allows to take implications for the future, in order to improve regional policies of integrated, balanced and efficient development through: (i) the definition of transparency and efficiency criteria in the application of the public money, (ii) the redesign of future policies for public investments, and (iii) the support to a more balanced inter-regional development.